Aplikasi Penilaian Kinerja Dosen Teknik Informatika - Syahrul Ramadan; Ade Hastuty; Mughaffir Yunus (Jurnal Informatika, 2024)
This research highlights the strategic role of lecturers in higher education, particularly in the teaching and assessment process. However, lecturer performance appraisals often contain elements of subjectivity that cause data inaccuracies. To overcome this, a technology-based system is needed that is able to support the decision-making process more objectively. The Simple Additive Weighting (SAW) method is used in this research because it is able to provide an assessment based on predetermined weights for each criterion. With this approach, the research aims to design a lecturer performance appraisal system that can improve the quality of education through more accurate and structured measurements.